Effective strategies for integrating e-learning in problem-based learning for engineering and technical education - Tasir, Zaidatun; Harun, Jamalludin; Syed Hassan, Syed Ahmad Helmi; Mohd. Yusof, Khairiyah (2007)

(untitled)
E-learning, through any Learning Management Systems (LMS), can be used to enhance and aid the implementation ofproblem-based learning (PBL). In UTM, an open-source LMS, Moodle, is being used. Through e-learning, learningcan take place anywhere and anytime through the communicationtools that it has. This feature provides a channel ofcommunication among students and lecturers that is not bounded by the class time and physical presence. Therefore, e-learning has been identified as a learning system that can greatly enhance the implementation of PBL among universitystudents. The purpose of this paper is to put forth effective strategies for utilizing e-learning in PBL for engineering andtechnical education. Some effective strategies that have been identified are:(1) the use of online assignment tool todeliver PBL problems to students, (2) the use of bothsynchronous communication tools (such as chatting) andasynchronous communications tools (suchas forum and journal) for discussionand assessment, (3) lecturer-initiatedcommunication for the PBL case on the e-learning platform, (4) frequent availability of lecturers online for facilitation,and (5) the use of online journal for reflection and assessment.These strategies enable a more efficient and effectiveimplementation of PBL.